The Relationship Between Preschool Teachers’ Proactive Personality and Innovative Behavior: The Chain-Mediated Role of Error Management Climate and Self-Efficacy - Baocheng Pan (Frontiers Media S.A., 2021)
Objective: This study, aims to explore the relationship of error management climate and self-efficacy between preschool teachers’ proactive personality and innovative behavior.Methods: Four hundred thirty-nine preschool teachers were tested by proactive personality scale, error management climate scale, general self-efficacy scale, and employee innovation behavior scale.Results: Preschool teachers’ proactive personality can directly predict their innovative behaviors, has a significant indirect effect on innovative behaviors through error management climate, and has a significant indirect effect on innovative behaviors through self-efficacy. Error management climate and self-efficacy play a chain-mediated role in the relationship between preschool teachers’ proactive personality and innovative behavior.Conclusion: Error management climate and self-efficacy play a chain-mediated role in the relationship between preschool teachers’ proactive personality and innovative behavior.